ANALISIS PENGARUH BIMBINGAN KELOMPOK TERHADAP MINAT BELAJAR SISWA DALAM PEMBELAJARAN DARING DI SMA NEGERI 1 NGUTER - Edmawati, Mahmuddah Dewi (Universitas PGRI Semarang, 2022)
AbstractInterest has an important role in the learning process, because with interest, students will be more concentrated, excited, happy, not easily bored, and earnest in learning. So that students achieve a learning success. Learning interest is influenced by internal and external factors. One of the external factors is parental support. Student interest in learning cannot be separated from the support of parents because parents are very important people with students.This study aims to determine the effect of student interest in learning at 1 Nguter Senior High School. This study used a literature study. Learning at Nguter 1 Public Senior High School uses online learning or what is commonly called distance learning (from home) with the guidance of parents and teachers at school. Students do online learning and interact with the teacher using several applications such as google classrooms, zoom rooms, and whatsapp groups. Students feel bored and bored when carrying out learning so there is a need for group guidance services to increase student interest in learning in online learning.Â Keywords : E-Learning, Interest to learn, Group GuidanceÂ Abstrak.Minat memiliki peran penting dalam proses pembelajaran, karena dengan minat siswa akan lebih konsentrasi, bersemangat, senang, tidak mudah bosan, dan tekun dalam belajar. Sehingga siswa mencapai keberhasilan belajar. Minat belajar dipengaruhi oleh faktor internal dan eksternal. Salah satu faktor eksternal adalah dukungan orang tua. Minat belajar siswa tidak lepas dari dukungan orang tua karena orang tua adalah orang yang sangat penting dengan siswa. Penelitian ini bertujuan untuk mengetahui pengaruh pembeljaran daring terhadap minat belajar siswa di SMA Negeri 1 Nguter. Penelitian ini menggunakan studi kepustakaan. Pembelajaran di SMA Negeri 1 Nguter menggunakan pembelajaran online atau biasa disebut pembelajaran jarak jauh (dari rumah) dengan bimbingan orang tua dan guru di sekolah. Siswa melakukan pembelajaran online dan berinteraksi dengan guru menggunakan beberapa aplikasi seperti google classrooms, zoom room, dan whatsapp group. Siswa merasa bosan dan jenuh saat melaksanakan pembelajaran sehingga perlu adanya layanan bimbingan kelompok untuk meningkatkan minat belajar siswa dalam pembelajaran daring.Â Katakunci : E-learning, Minat belajar, Bimbingan Kelompok